Evaluating the impact of different positron emitters on the performance of a clinical PET/MR system. Issue 4 (17th February 2022) - Meng, Xiangxi; Liu, Hui; Li, Hui; Wang, Shujing; Sun, Hongwei; Wang, Feng; Ding, Jin; He, Liuchun; Chen, Xin; Jin, Lujia; Dong, Yun; Zhu, Hua; et al.
Abstract: Purpose: The positron range and prompt gamma emission are distinctive with different positron emitters. The performance assessment of an integrated PET/MR scanner with these positron emitters is required for related applications, as the magnetic field interferes with the positron propagation. Such an assessment is to be performed on the United Imaging uPMR 790‐integrated PET/MR system. Methods: The performance measurement methods were modified based on NEMA NU 2‐2012, involving 18 F, 64 Cu, 68 Ga, 89 Zr, and 124 I as positron emitters. The NEMA IEC phantom was used for evaluations of image qualities. An agarose cap was wrapped around the point source for tissue‐simulating spatial resolution measurement. The count rate performance was assessed with selected positron emitters. Images of a 3D‐printed Derenzo phantom and representative patients were also acquired. Results: The image quality measurement showed that all five positron emitters were suitable for the PET/MR system studied. However, due to the magnetic field, the image of the point source showed an elongated comet‐tail feature, which could be eliminated by a tissue‐simulating cap. This effect is more obvious in 124 I and 68 Ga, due to their long positron ranges. The imaging ability with various positron emitters was further validated with the count rate assessment, the Derenzo phantom, and the clinical images. Conclusions: Different positron emitters could be effectively imaged by the PET/MR system tested. The resolution measurement strategy proposed could be applied to measure PET spatial resolution in the magnetic field.